Issues in which the Dispute in the Hanbali Doctrine is Collected and Discuss Denied in the Chapter if the Company through the Book of Al-Ensaf to Mardawi. (Die: 885( - Mona Mansour Ahmed AL-Moud; Dr. Hind Saad Saeed Al-Qahtani (Miasto Przyszłości, 2023)
The Hanbali school spoke of many provisions and issues written in all sections of the doctrine where they were likely to be based on evidence and others, excluded from them and confined to books of their own. Among those issues of jurisprudence, Hanbal often mentions in their books the Convention, and expresses them in terms of that agreement and thus denies disagreement in the doctrine, so that I would like to establish whether or not to deny the dispute, so that it can be easily consulted, there was a research project entitled: (Issues where disagreement in Hanbali doctrine has been resolved collectively and studied in the doors of: Agency, Company, Bartaining, Farming, Rent, and Predecessor through the Book of Equity for the Murdawi). I have gathered the scattered issues of the writings of the scholars of Hanbal in the said sections so that I can achieve the denial of disagreement in these matters in a clear easy way, but I have chosen to replace the door of the company because of the conditions of publication of scientific articles on the one hand and the importance of the topic of companies in our contemporary reality.